Comparison of organic carbon from humic and fulvic acids and the degree of humification in five soil orders - Sardón Nina, Sandro (2021)
This study compared the organic carbon (OC) content in fractions of humic acids (HA) and fulvic acids (FA) in five soil orders (Aridisol, Entisol, Histosol, Inceptisol and Mollisol) and know their association with the degree of humification. Extraction and fractionation, as well as the degree of humification was carried out by the Nagoya method proposed by Kumada. OC quantification was determined by the Walkley and Black method. The results are: the average OC content of HAs of the order Aridisol differs from that of Histosols, Inceptisols, and Mollisols. The order Entisol presented differences with the Histosols and Mollisols, the soils of the order Inceptisol presented differences with the Aridisols and Histosols and those of the order Histosol differed from the Aridisols, Entisols and Inceptisols. Similarly, those of the Mollisol order differed with the Aridisols, Entisols and Inceptisols. In the fraction of FA the average OC content of the order Aridisol deferred from that found in Histosols, Inceptisols and Mollisols. The Entisol order differed from the Mollisols; likewise, the Inceptisol order differed from the Aridisols and Mollisols and the Histosol order differed from the Aridisols. Finally, the order Mollisol was also different from the Aridisols, Entisols, and Inceptisols. Soil types do not show wetting patterns, because they are not based on pedogenetic processes and these have a wide range of characteristics in surface horizons.